2012
DOI: 10.3102/0013189x12442983
|View full text |Cite
|
Sign up to set email alerts
|

Translating Autoethnography Across the AERA Standards

Abstract: The purpose of this article is to move readers toward a deeper understanding of and widened respect for autoethnography's capacity as an empirical endeavor. An argument is presented in favor of autoethnography as empirical by translating information from its epistemological and methodological history across the AERA standards for reporting empirical social science research.Supporting evidence is drawn from samples of autoethnographic scholarship that emerged from an extensive literature review of first-tier, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(17 citation statements)
references
References 38 publications
(97 reference statements)
0
17
0
Order By: Relevance
“…The participants share roles in this study as participant observers in the study with a responsibility for untangling a phenomenon or multiple phenomena which engulf a specific institutional leadership role in higher education-that of the department head (Gunsalus, 2006;Buller, 2015). The appropriate method for this role is a dialogic and biographical-ethnographic form of phenomenological methods (Garza, 2008;Hughes et al, 2012;Lund et al, 2012;Hoppes, 2014). These methods fit the classification of emergent (sometimes deemed qualitative) research design (Pasque et al, 2011(Pasque et al, , 2013Saldaña, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The participants share roles in this study as participant observers in the study with a responsibility for untangling a phenomenon or multiple phenomena which engulf a specific institutional leadership role in higher education-that of the department head (Gunsalus, 2006;Buller, 2015). The appropriate method for this role is a dialogic and biographical-ethnographic form of phenomenological methods (Garza, 2008;Hughes et al, 2012;Lund et al, 2012;Hoppes, 2014). These methods fit the classification of emergent (sometimes deemed qualitative) research design (Pasque et al, 2011(Pasque et al, , 2013Saldaña, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The ultimate goal of autoethnography is to connect “the personal” with “the social” (Adams et al, 2014; Chang, 2008; Cook, 2014; Denzin, 2014; Ellis, Adams, & Bochner, 2011; Holman Jones, Adams, & Ellis, 2015; Reed-Danahay, 1997). Hughes, Pennington, and Makris (2012) articulated the importance of connecting these two elements in autoethnography as such: [A]uto-ethnography is . .…”
Section: Autoethnography As a Qualitative Inquirymentioning
confidence: 99%
“…Nevertheless, whichever methods social scientists use to conduct their research, they are expected to reveal their research process and procedures transparently so that readers can see clearly how they have arrived at their conclusions. Hughes et al (2012) articulated the American Educational Research Association’s (AERA) standard of publishing and demonstrated how autoethnography could meet the AERA’s standard of presenting the research process in their research reports. Many qualitative researchers, particularly autoethnographers, have not been too diligent about revealing and discussing their research methodology.…”
Section: Autoethnography As a Qualitative Inquirymentioning
confidence: 99%
See 2 more Smart Citations